Multiple Modes of Vitamin K Actions in Aging-Related Musculoskeletal Disorders - Azuma, Kotaro; Inoue, Satoshi (International journal of molecular sciences, 2019)
Vitamin K is a fat-soluble vitamin that was originally found as an essential factor for blood coagulation. With the discovery of its role as a co-factor for γ-glutamyl carboxylase (GGCX), its function for blood coagulation was understood as the activation of several blood coagulation factors by their γ-carboxylation. Over the last two decades, other modes of vitamin K actions have been discovered, such as the regulation of transcription by activating the steroid and xenobiotic receptor (SXR), physical association to 17β-Hydroxysteroid dehydrogenase type 4 (17β-HSD4), covalent modification of Bcl-2 antagonist killer 1 (Bak), and the modulation of protein kinase A (PKA) activity. In addition, several epidemiological studies have revealed that vitamin K status is associated with some aging-related diseases including osteoporosis, osteoarthritis, and sarcopenia. Clinical studies on single nucleotide polymorphisms of GGCX suggested an association between higher GGCX activity and bone protective effect, while recent findings using conditional knockout mice implied that a contribution in protective effect for bone loss by GGCX in osteoblastic lineage was unclear. GGCX in other cell lineages or in other tissues might play a protective role for osteoporosis. Meanwhile, animal experiments by our groups among others revealed that SXR, a putative receptor for vitamin K, could be important in the bone metabolism. In terms of the cartilage protective effect of vitamin K, both GGCX- and SXR-dependent mechanisms have been suggested. In clinical studies on osteoarthritis, the γ-carboxylation of matrix Gla protein (MGP) and gla-rich protein (GRP) may have a protective role for the disease. It is also suggested that SXR signaling has protective role for cartilage by inducing family with sequence similarity 20a (Fam20a) expression in chondrocytes. In the case of sarcopenia, a high vitamin K status in plasma was associated with muscle strength, large muscle mass, and high physical performance in some observational studies. However, the basic studies explaining the effects of vitamin K on muscular tissue are limited. Further research on vitamin K will clarify new biological mechanisms which contribute to human longevity and health through the prevention and treatment of aging-related musculoskeletal disorders.